Public Service Quality Analysis at the Population and Civil Registration Office of Manado City - Kamoda, Aprillio P. D. A.; Tulusan, Femmy M. E.; Tampi, Johny R. E. (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the quality of public services at the Manado City Population and Civil Registry Office. The research used a qualitative approach. The research will be carried out for approximately 3 months. The focus of research on public services based on the dimensions of service quality which consists of three indicators, namely responsiveness, responsibility, and accountability. Informants in the study amounted to 10 people. Data was gathered through observations, conducting interviews, and reviewing documents. Data analysis, as described by Miles and Huberman, involves a few key steps: reducing the data, presenting it, and then drawing conclusions or verifying findings. Research on service quality using responsiveness indicators reveals that the main issue raised by the public is long lines and wait times. People also complain about the lack of information on document requirements, processes, and service times. Other issues include a lack of transparency, slow service, and minimal communication from service officers. The responsibility indicator shows that the Manado City Dukcapil Office has problems in administrative procedures where there are many stages that must be passed and are often not clearly explained to the public. Human resources at the serving offices are insufficient to handle the high number of people, resulting in a slow process. Many individuals do not have the necessary documents because they are unaware of the requirements. The accountability indicator shows that Disdukcapil Manado City is committed to providing guaranteed public services that can be accessed easily, on time, accurately, safely and fairly.